Zelotes kukushkini sp. n. (Aranei, Gnaphosidae) и близкие виды в фауне Палеарктики - Ковблюк, Н.М. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2006)
Описан Zelotes kukushkini Kovblyuk, sp. n. с юга Украины, который отличается от ближайших видов из Палеарктики — Z. subterraneus (C. L. Koch, 1833), Z. fratris Chamberlin, 1920, Z pyrenaeus Di Franco et Blick, 2003 и Z. sula Lowrie et Gertsch, 1955 — формой эмболюса (короче, чем у Z. subterraneus и Z. fratris, но длиннее, чем у Z. pyrenaeus и Z. sula) и строением всего эмболярного отдела бульбуса, а также формой эпигины и каналов семяприемников. Эпигина и вульва самки нового вида очень похожи на таковые у Z. fratris. Все упомянутые виды, кроме Z. pyrenaeus, переописаны и иллюстрированы. Zelotes kukushkini Kovblyuk, sp. n. from the South of Ukraine is described. It differs
from related Palaearctic species — Z. subterraneus (C. L. Koch, 1833), Z. fratris Chamberlin, 1920,
Z. pyrenaeus Di Franco et Blick, 2003 and Z. sula Lowrie et Gertsch, 1955 by the shape of the embolus
(shorter than in Z. subterraneus and Z. fratris, but longer than in Z. pyrenaeus and Z. sula — by the
structure of embolar division of bulbus, and by the shape of epigyne and spermathecae canals. The
structure of the epigyne and spermathecae of Zelotes kukushkini sp. n. are similar to those of Z. fratris.
All the species (except Z. pyrenaeus) are redescribed and figured.